Comparison of ropivacaine 0.5% with dexmedetomidine and clonidine as adjuvants in ultrasound-guided infraclavicular brachial plexus block for upper limb surgery - Kiwi Mantan; Rakesh; Sandeep Kothari; T. Agalya; Anita Pareek; Neha Chahar; Bhanupriya (Creative Pharma Assent, 2023)
Background: The Institutional Ethics Committee and patients' informed written consent were obtained before this study was carried out in the Department of Anaesthesiology at Sardar Patel Medical College in Bikaner, Rajasthan. An established method for delivering anaesthesia and analgesia during upper limb surgery is brachial plexus block. For peripheral nerve blocks, ropivacaine, a long-acting amide with a safe cardiac profile, is chosen. It has been proven that different adjuncts may be added to LA solutions to boost their effectiveness and longevity while lowering the overall dose of LA utilised and minimising any systemic side effects. Our goal was to assess the effectiveness of adjuvants such as dexmedetomidine and clonidine in comparison to 0.5% ropivacaine in an infraclavicular block for upper limb surgery under USG guidance. Method: Fifty adult patients planned for elective upperlimb surgery with an infraclavicular brachial plexus block under USG guidance were included. All research participants were split into two groups at random. In groups D and C, respectively, dexmedetomidine and clonidine were used as adjuvants with 0.5% ropivacaine. Our main goal was to compare the postoperative analgesic duration in both research groups, as well as the onset and duration of sensory and motor block. Patients were monitored for any complications connected to the medicine and procedure while hemodynamic indicators were also compared. Results: Group D's sensory and motor block action initiation time was substantially quicker than that of group C's (p 0.001). When compared to Group C, Group D's sensory and motor block and postoperative analgesia durations were considerably longer (p value 0.001). Conclusion: Dexmedetomidine is a more effective adjuvant than clonidine when given during upper limb surgery with an infraclavicular block that is guided by a USG.